Conductance Measurement of Water-sorbed Activated Carbon - Badri, M.; Crouse, Karen Anne; Awang, Harun (1984)
The conductance of a piece of I1ctivated carbon has been measured while immersed under water at five different temperatures. The change in conductance with time has been attributed to the ionization of the functional groups on the walls of the pores as the latter were gradually filled. The average pore radius has been estimated by using the equations derived to relate the increase in the conductance to the rate of flow of water into the pores.